Efficient nutrient removal from low C/N municipal wastewater using a phototrophic biofilm system integrating simultaneous nitrification–denitrification and phosphorus removal (SND) - Qingan Meng; Wei Zeng; Jiayu Zhang; Hongjun Liu; Shuangshuang Li; Yongzhen Peng (Environmental Research, 2026)

Tidal current-induced local scour around offshore tripile foundations: A CFD study of flow-structure-sediment interaction - Hongjun Liu; Wei He; Qi Yang; Lu Jing; Peng Yu; Xinyu Liu; Jieru Zhao (Ocean Engineering, 2026)

Unregulated delayed emissions dominate ultrafine particles from modern diesel vehicles - Fuyang Zhang; Jianfei Peng; Peiji Liu; Yajun Wu; Jinsheng Zhang; Jiayuan Liu; Kexin Liu; Bin Sun; Qijun Zhang; Lin Wu; Ning Yang; Miao Tang; et al. (Journal of Hazardous Materials, 2026)

Targeting delivery of shikonin via cryo-shocked tumor cells for non-small cell lung cancer treatment - Huanhuan Huang; Hui Ren; Feiye Liu; Wenyue Lv; Mengzhen Xu; Huiheng Feng; Haoli Liu; Dong Chen; Peng Zhao; Hongjun Li; Jing Qin (Chemical Engineering Journal, 2026)

Health risks from PM2.5-bound heavy metals from religious burning activities on the plateau - Zhaoquan Yu; Lei Yang; Jiawei Yin; Haomiao Niu; Zhou Xu; Hao Qin; Liuyang Guo; Yan Liu; Lin Wu; Qijun Zhang; Jianfei Peng; Hongjun Mao (Journal of Hazardous Materials, 2026)

Evaluating the effectiveness of tightened emission standards in reducing real-world vehicle emissions: Evidence from on-road testing and inventory analysis - Lei Yang; Zhaoquan Yu; Haomiao Niu; Hao Qin; Jiawei Yin; Zhou Xu; Yan Liu; Lin Wu; Jianfei Peng; Hongjun Mao; Qijun Zhang (Journal of Cleaner Production, 2026)

Mineral-associated organic carbon promotes phosphorus accumulation in a long-term fertilized black soil - Naiyu ZHANG; Xiuzhi ZHANG; Yanhua CHEN; Lehlogonolo Abner MATELELE; Ping ZHU; Hongfang LIU; Xianmei ZHANG; Hongjun GAO; Gu FENG; Chang PENG; Shuxiang ZHANG (Pedosphere, 2026)

Liquid fuel intrusion causes carbon canister deterioration and excess evaporative VOC emissions from in-use vehicles - Pengfei Song; Yan Liu; Qiang Chen; Jingyu Liu; Xueying Zeng; Tianlong Xing; Rui Zhang; Chongzhi Zhong; Taiyu Zhang; Ning Yang; Jianfei Peng; Hongjun Mao (Journal of Hazardous Materials, 2026)

Real-world key-process emission factors optimized environmental impact from passenger car tires’ PM2.5 and typical chemicals throughout lifecycle - Tiange Fang; Lei Sheng; Qiang Zeng; Guang Yang; Jinsheng Zhang; Wendi Wei; Jianfei Peng; Lin Wu; Ting Wang; Jing Zhang; Hongjun Mao (Journal of Hazardous Materials, 2026)

Metagenomic insights into the survival strategy of Tetrasphaera under prolonged anaerobic conditions: transition from polyphosphate metabolism to fermentation - Zhaoyang Bi; Wei Zeng; Hongjun Liu; Jiayu Zhang; Wenzhuo Jiang; Yongzhen Peng (Chemical Engineering Journal, 2026)

Upcycling industrial waste bischofite to anti-aging agents for asphalt: Macro-properties, micro-characteristics, and statistics-based mechanistic analysis - Hongjun Dong; Zihang Li; Canlin Zhang; Chiara Riccardi; Ting Wang; Peng Jin; Yan Yuan (Chemical Engineering Journal, 2026)

Revealing denitrifying phosphorus removal metabolic diversity and FNA tolerance of Tetrasphaera with nitrate and nitrite as electron acceptors - Jiayu Zhang; Wei Zeng; Qingan Meng; Hongjun Liu; Yao Lu; Zhaoyang Bi; Yongzhen Peng (Chemical Engineering Journal, 2026)

Ammonia emission from real-world in-use vehicle fleets in a megacity in China - based on tunnel measurement - Jiliang Guo; Jinsheng Zhang; Ainan Song; Hui Tong; Jingchun Tang; Ning Yang; Zhuofei Du; Qijun Zhang; Ting Wang; Lin Wu; Jianfei Peng; Hongjun Mao (Journal of Environmental Sciences, 2026)

Tunable surface potential nanomaterials for enhanced environmental nucleic acid extraction and surveillance - Jiahui Lv; Tong Li; Ying Liu; Bing Li; Peng Jia; Chuwei Ma; Hongjun Xiao; Guanghui Wang; Li Cheng; Jingkai Yang; Ziyi Xu; Xuan Tan; et al. (Water Research, 2025)

Experimental investigation of the hydrodynamic response of a cantilevered gas-conveying flexible tube - Hongjun Zhu; Peng Liu; Yue Gao; Lin Ding; Tongming Zhou (Ocean Engineering, 2025)

Characterizations of air pollutants at roadside monitoring stations and traffic emission effects: A case study in Tianjin, China - Fangyuan Zheng; Junxia Gao; Lin Wu; Naixiu Sun; Wentian Xu; Qijun Zhang; Hongjun Mao; Jianfei Peng; Liwei Li; Ning Yang; Bin Liu (Journal of Environmental Sciences, 2025)

UAVO-NeRF: 3D reconstruction of orchards and semantic segmentation of fruit trees based on neural radiance field in UAV images - Hongxing Peng; Shangkun Guo; Xiangjun Zou; Hongjun Wang; Juntao Xiong; Qijun Liang (Computers and Electronics in Agriculture, 2025)

Unrecognized emissions and health risks of intermediate-volatility organic compounds in vehicle cabins: Insights from a nontargeted analytical approach - Haoning Chang; Yajun Wu; Jing Zhang; Dianjia Liu; Yao Zeng; Pengfei Song; Jinsheng Zhang; Yan Liu; Lin Wu; Ting Wang; Hongjun Mao; Jianfei Peng; et al. (Journal of Hazardous Materials, 2025)

Refinement of vehicle emission factor estimation in tunnel experiments using CFD and field measurement - Xiaoyu Liang; Jianfei Peng; Yan Liu; Jinsheng Zhang; Lin Wu; Hongjun Mao (Environmental Pollution, 2025)

Insights into synergistic metabolism mechanisms of carbon, nitrogen and phosphorus in Tetrasphaera-dominated partial denitrifying phosphorus removal and anammox (PDPRA) process - Jiayu Zhang; Wei Zeng; Qingan Meng; Hongjun Liu; Yao Lu; Shuangshuang Li; Yongzhen Peng (Water Research, 2025)

Excess vehicular evaporative emissions for prolonged parking during the COVID-19 lockdown in China - Pengfei Song; Jianfei Peng; Yan Liu; Chongzhi Zhong; Qiang Chen; Chao Zou; Shida Sun; Yajun Wu; Yao Gu; Taiyu Zhang; Ning Yang; Hongjun Mao (Journal of Hazardous Materials, 2025)

Declining floral color diversity alters bee color preferences in fragmented habitats - Hongjun Xie; Peng Ren; Chen Zhu; Juan Liu; Minghao Sun; Xingfeng Si; Ping Ding (Biological Conservation, 2025)

Environmental benefit assessment of vehicle electrification in the fuel cycle: A case study of Chengdu - Zhaoyang Fan; Hui Tong; Naixiu Sun; Yangxin Xiong; Xuan Qu; Hongjun Mao; Jianfei Peng (Atmospheric Environment, 2025)

Integrated process of Tetrasphaera-dominated enhanced biological phosphorus removal and sulfur autotrophic denitrification in a single reactor to treat VFAs-free wastewater: Feasibility, performance and mechanism - Hongjun Liu; Wei Zeng; Gangxin Chen; Qingan Meng; Jiayu Zhang; Zhaoyang Bi; Yongzhen Peng (Journal of Water Process Engineering, 2025)

Contribution of Vehicular Evaporative S/IVOC emission to SOA formation in China - Zhaoyang Fan; Yajun Wu; Yuwei Xie; Hui Tong; Naixiu Sun; Pengfei Song; Wentian Xu; Yan Liu; Shaojie Song; Hongjun Mao; Jianfei Peng (Atmospheric Environment, 2025)

Fluxapyroxad induces chronic colonic inflammation via inhibiting intestinal aryl hydrocarbon receptors in mice - Yue Cao; Shouchun Xiao; Yaofeng Fang; Jiaxing Yang; Zeyu Hu; Hongjun Zhang; Xueke Liu; Donghui Liu; Zhiqiang Zhou; Peng Wang (Science of The Total Environment, 2025)

L-cysteine modulates the Maillard reaction: Impacts on PhIP and pyrazine formation - Xiaoran Chu; Pengfei Du; Weiting Wang; Hongjun He; Peng Hu; Yaobo Liu; Min Li; Wenxiang Jiang; A.M. Abd El-Aty (Food Chemistry, 2025)

Mechanical Properties and Microstructure Characteristics of Submerged Cement-Based Stabilized Marine Soft Clay Enhanced with ISS and PAM - Chenghao Zhu; Peng Yu; Zixian Guo; Qigang Wang; Hongjun Liu (Journal of Ocean University of China, 2025)

Enhancing ozone catalytic decomposition through acid treatment of α-MnO2 for improved activity and humidity resistance - Shangchao Xiong; Kai Zhang; Zhenghao Xu; Hongjun Ou; Yuanyuan Zheng; Xi Li; Yue Peng; Xubiao Luo; Junhua Li (Journal of Environmental Sciences, 2025)

A novel method to improve the anti-ageing ability of bitumen by organic LDHs/SBS composite: Preparation, performance evaluation and mechanism analysis - Canlin Zhang; Shuai Yang; Ting Wang; Song Xu; Peng Jin; Hongjun Dong; Yi Zhang; Yu Chen (Fuel, 2025)

Size distribution, chemical composition and influencing factors of vehicle tire wear particles based on a novel test cycle - Qijun Zhang; Jiawei Yin; Zeping Cao; Tiange Fang; Jianfei Peng; Lin Wu; Hongjun Mao (Environmental Research, 2025)

Drought risk assessment for maize/peanut intercropping based on crop model and SPEI - Yajiaoxue Guo; Zhanxiang Sun; Wei Bai; Zhe Zhang; Yue Zhang; Hongjun Du; Tianran Sun; Jinyu Zhang; Pu Peng; Yafei Ji; Qian Cai; Zhi Dong; et al. (Agricultural Systems, 2024)

Integrated process of Tetrasphaera-dominated in-situ waste activated sludge fermentation, biological phosphorus removal and endogenous denitrification in single reactor for treatment of wastewater with limited carbon sources - Hongjun Liu; Wei Zeng; Lei Wu; Qingan Meng; Jiayu Zhang; Yongzhen Peng (Bioresource Technology, 2024)

Preservation effects of chitosan/polyvinyl alcohol/clove essential oil antifungal film on yellow peaches: Physicochemical properties and fruit quality assessment - Liyuan Wang; Hongjun Fu; Qian Tan; Siyu Wu; Yan Wang; Xianglian Peng (Food Control, 2024)

Nonnegligible contribution of terrigenous sediment inputs from local small watersheds to west regions of the Pearl River Estuary, northern South China Sea shelf - Chenjian He; Tingping Ouyang; Mingkun Li; Shanying Zhu; Mingjie Yu; Shasha Peng; Zhaoyu Zhu; Yunpeng Wang; Hongjun Chen; Chengjing Tian (Marine Geology, 2024)

Insights into in situ surface reconstruction in cobalt perovskite oxides for enhanced catalytic activity - Yanyu Jin; Hongjun Cheng; Qibao Wang; Xiaoqing Liu; Shengpeng Mo; Bin Zhou; Yue Peng; Yu Wang; Wenzhe Si; Junhua Li (Journal of Hazardous Materials, 2024)

Site database for national strong motion stations in mainland China - Kun Ji; Yefei Ren; Chuanbin Zhu; Yuting Zhang; Xinxin Yao; Daren Wang; Peng Zhang; Hongjun Si; Tadahiro Kishida; Ye Liu; Saman Yaghmaei-Sabegh; Ruizhi Wen (Engineering Geology, 2024)

A spatiotemporal synergetic operating performance assessment based on reconstructed correlation matrix and dissimilarity analytics for plant-wide hot strip mill process - Chuanfang Zhang; Hongjun Zhang; Kaixiang Peng; Jie Dong; Hanwen Zhang; Xueyi Zhang (Process Safety and Environmental Protection, 2024)

Masting promotes transformation from predation to mutualism in an oak-weevil-rodent system - Hongmao Zhang; Hongyu Niu; Michael A. Steele; Liqing Peng; Huimin He; Aoqiang Li; Xianfeng Yi; Hongjun Li; Zhibin Zhang (Science China Life Sciences, 2024)

Atmospheric environment characteristic of severe dust storms and its impact on sulfate formation in downstream city - Naixiu Sun; Lin Wu; Fangyuan Zheng; Danni Liang; FuYuan Qi; Shaojie Song; Jianfei Peng; Yufen Zhang; Hongjun Mao (Science of The Total Environment, 2024)

Tailpipe volatile organic compounds (VOCs) emissions from Chinese gasoline vehicles under different vehicle standards, fuel types, and driving conditions - Peiji Liu; Yajun Wu; Zongxuan Li; Zongyan Lv; Jinsheng Zhang; Yan Liu; Ainan Song; Ting Wang; Lin Wu; Hongjun Mao; Jianfei Peng (Atmospheric Environment, 2024)

Transforming waste brake pads from automobiles into Nano-Catalyst: Synergistic Fe-C-Cu triple sites for efficient fenton-like oxidation of organic pollutants - Fuyuan Qi; Jianfei Peng; Zilu Liang; Jiliang Guo; Jiawei Yin; Ainan Song; Zongxuan Li; Jiayuan Liu; Tiange Fang; Jinsheng Zhang; Lin Wu; Qijun Zhang; et al. (Waste Management, 2024)

Investigating the impact of high-altitude on vehicle carbon emissions: A comprehensive on-road driving study - Zhiwen Jiang; Lin Wu; Haomiao Niu; Zhenyu Jia; Zhaoyu Qi; Yan Liu; Qijun Zhang; Ting Wang; Jianfei Peng; Hongjun Mao (Science of The Total Environment, 2024)

An integrated system combining Tetrasphaera-dominated enhanced biological phosphorus removal with sulfur autotrophic denitrification to enhance biological nutrients removal - Hongjun Liu; Wei Zeng; Qingan Meng; Jiayu Zhang; Yongzhen Peng (Science of The Total Environment, 2024)

Regenerative braking system effectively reduces the formation of brake wear particles - Qijun Zhang; Jiawei Yin; Tiange Fang; Quanyou Guo; Jiaxing Sun; Jianfei Peng; Chongzhi Zhong; Lin Wu; Hongjun Mao (Journal of Hazardous Materials, 2024)

Long-term Fertilizer Application Induces Changes in Carbon Storage and Distribution, and the Consequent Color of Black soil - Jichao Gao; Lichun Wang; Jiafa Luo; Hongjun Gao; Weiwen Qiu; Qiang Li; Xiuzhi Zhang; Ping Zhu; Chang Peng; Yunfei Jiao; Lingying Xu (Journal of Soil Science and Plant Nutrition, 2024)

Effects of childhood maltreatment and major depressive disorder on functional connectivity in hippocampal subregions - Huiqin Nie; Tong Yu; Yurong Zou; Yuhong Li; Juran Chen; Jinrou Xia; Qianyi Luo; Hongjun Peng (Brain Imaging and Behavior, 2024)

Experimental study of structure dimensions effects on local scour of submerged compound suction anchor foundation - Chenghao Zhu; Wenyu Wu; Xiaoli Liu; Hongjun Liu; Ruigeng Hu; Peng Yu (Ocean Engineering, 2024)

Experimental and numerical investigation on the impact of MS2AF on local scour protection performance - Chenghao Zhu; Qiheng Li; Jianguo Zheng; Hongjun Liu; Peng Yu (Ocean Engineering, 2024)

Environmental impacts of potential mining-replacing-import alternative for China in response to the China-Australia coal ban - Zhaoyang Fan; Xin Ju; Hui Tong; Zilu Liang; Naixiu Sun; Hongjun Mao; Jianfei Peng (Journal of Cleaner Production, 2024)

Optimizing sludge retention time for sustainable photo-enhanced biological phosphorus removal systems: Insights into nutrient fate, microbial community, and bacterial phototolerance - Qingan Meng; Wei Zeng; Hongjun Liu; Jiayu Zhang; Biao Ma; Yongzhen Peng (Journal of Environmental Management, 2024)

Direct measurement of brake and tire wear particles based on real-world driving conditions - Qijun Zhang; Tiange Fang; Zhengyu Men; Ning Wei; Jianfei Peng; Tianqiang Du; Xinfeng Zhang; Yao Ma; Lin Wu; Hongjun Mao (Science of The Total Environment, 2024)

Green technology outsourcing for agricultural supply chains with government subsidies - Ligang Shi; Tao Pang; Hongjun Peng; Xin Feng (Journal of Cleaner Production, 2024)

Effects of triclosan exposure on stem cells from human exfoliated deciduous teeth (SHED) fate - Shiwen Deng; Caifeng Li; Junqi Chen; Zhao Cui; Tong Lei; Hongjun Yang; Peng Chen (Science of The Total Environment, 2023)

A Cryogenian interglacial source rock in South China: Geochemistry, spatial distribution and organic matter enrichment - Peng Li; Hongjun Qu; Aiguo Wang; Shuo Chen (Precambrian Research, 2023)

Fabrication of a novel acid-resistant nanofiltration membrane with dual-charged functional layer for metal ions recovery - Lu Bai; Zhilu Li; Zhengjun Peng; Youjing Zhao; Hongjun Yang; Min Wang (Journal of Environmental Chemical Engineering, 2023)

Chemical characteristics of fine tire wear particles generated on a tire simulator - Quanyou Guo; Zhengyu Men; Zhenguo Liu; Zhihui Niu; Tiange Fang; Fengyang Liu; Lin Wu; Jianfei Peng; Hongjun Mao (Environmental Pollution, 2023)

Enhanced biological phosphorus removal systems adapting to seawater intrusion: Impacts of varying carbon source on metabolic adaptation in Candidatus Accumulibacter phosphatis - Qingan Meng; Wei Zeng; Mengjia Zhan; Hongjun Liu; Jiayu Zhang; Xianchun Lu; Yongzhen Peng (Chemical Engineering Journal, 2023)

Denitrifying phosphorus removal (DPR) performance and metabolic mechanisms of Tetrasphaera at long-term nitrite exposure - Jiayu Zhang; Wei Zeng; Qingan Meng; Hongjun Liu; Sijia Lu; Yongzhen Peng (Chemical Engineering Journal, 2023)

Green light optimized speed advisory achieves fuel savings and CO2 emission reduction by profoundly impacting driving behavior - Xiaoyang Zhao; Zhenyu Jia; Ning Wei; Dongping Guo; Lu Yao; Jiawei Yin; Lin Wu; Yanjie Zhang; Jianfei Peng; Ting Wang; Zhiwen Yang; Qijun Zhang; et al. (Journal of Cleaner Production, 2023)

Extracellular vesicles from human umbilical cord mesenchymal stem cells prevent steroid-induced avascular necrosis of the femoral head via the PI3K/AKT pathway - Puji Peng; XueZhong Wang; Chen Qiu; Wendi Zheng; Hongjun Zhang (Food and Chemical Toxicology, 2023)

Innovative role of polyvinylpyrrolidone in tailoring polyamide layer for high-performance nanofiltration membranes - Zhiwen Li; Shuilian Peng; Wentian Zhang; Jianzhen Zhang; Yang Jiao; Renjie Li; Liguo Shen; Hongjun Lin; Yanchao Xu (Desalination, 2023)

Anti-ice-pinning superhydrophobic surfaces for extremely low ice adhesion - Ze Tian; Peixun Fan; Dongyu Zhu; Lizhong Wang; Huanyu Zhao; Changhao Chen; Rui Peng; Daizhou Li; Hongjun Zhang; Minlin Zhong (Chemical Engineering Journal, 2023)

Genetic sequencing provides insights into molecular and genetic mechanisms of Lysobacter enzymogenes HYP18 involved in soil organic nitrogen and phosphorus mobilization and plant growth promotion - Liyuan Peng; Jianguo Huang; Chunyang Huang; Hongjun Yang (Plant and Soil, 2023)

Carbon quantum dots in-situ relieve humic acids inhibition on methanogens while significantly increasing the abundance of Methanosarcinaceae - Qiang Liu; Yuanting Xu; Yeqing Li; Chengjie Ma; Shuo Chen; Lu Feng; Quan Xu; Junting Pan; Bo Peng; Hongjun Zhou; Chunming Xu (Journal of Cleaner Production, 2023)

Real world emission characteristics of Chinese fleet and the current situation of underestimated ship emissions - Lei Yang; Qijun Zhang; Zongyan Lv; Jingbo Zhao; Chao Zou; Ning Wei; Zhenyu Jia; Yanjie Zhang; Fei Fu; Jianhua Lv; Lin Wu; Ting Wang; et al. (Journal of Cleaner Production, 2023)

Particulate emissions from gasoline vehicles using three different fuel injection technologies - Zongyan Lv; Jianfei Peng; Jinsheng Zhang; Lei Yang; Dongping Guo; Ning Wei; Yajun Wu; Tiange Fang; Ainan Song; Chaoyang Fan; Lin Wu; Qijun Zhang; et al. (Journal of Cleaner Production, 2023)

Heavy vehicles’ non-exhaust exhibits competitive contribution to PM2.5 compared with exhaust in port and nearby areas - Tiange Fang; Ting Wang; Chao Zou; Quanyou Guo; Jianhua Lv; Yanjie Zhang; Lin Wu; Jianfei Peng; Hongjun Mao (Environmental Pollution, 2023)

Evaluating vehicular exhaust and evaporative emissions via VOC measurement in an underground parking garage - Yajun Wu; Yan Liu; Peiji Liu; Luna Sun; Pengfei Song; Jianfei Peng; Ruikang Li; Ning Wei; Lin Wu; Ting Wang; Lina Zhang; Ning Yang; et al. (Environmental Pollution, 2023)

Characteristics, sources, and health risks of inorganic elements in PM2.5 and PM10 at Tianjin Binhai international airport - Qijun Zhang; Lei Yang; Jianfei Peng; Lin Wu; Hongjun Mao (Environmental Pollution, 2023)

Energy saving and emission reduction effects from the application of green light optimized speed advisory on plug-in hybrid vehicle - Zhenyu Jia; Ning Wei; Jiawei Yin; Xiaoyang Zhao; Lin Wu; Yanjie Zhang; Jianfei Peng; Ting Wang; Zhiwen Yang; Qijun Zhang; Hongjun Mao (Journal of Cleaner Production, 2023)

Softening/Hardening Damage Model and Numerical Implementation of Seabed Silt-Steel Interface in Yellow River Underwater Delta - Peng Yu; Honghua Liu; Lin Geng; Shuai Wang; Yang Yu; Chenghao Zhu; Qi Yang; Hongjun Liu; Yong Guan (Journal of Marine Science and Engineering, 2023)
The interaction between soil and structure is a research hotspot in ocean engineering, and the shear performance of interfaces is an essential factor affecting the bearing capacity of offshore structures. Taking the Yellow River Underwater Delta as the research area, the Softening/Hardening damage model of the silt–steel interface and the determination method of model parameters are proposed based on the statistical damage theory. Through the interface monotonic shear test under the conditions of different normal stress, roughness and water content, the shear mechanical properties and volumetric deformation laws on the silt–steel interface are analyzed, and the damage model parameters are obtained. Finally, a FRIC subroutine for the damage model was developed based on ABAQUS. The research results indicate the following: (1) The interface between silt and steel exhibits two characteristics, softening/hardening and shear shrinkage/expansion, under different conditions. Roughness significantly impacts interfacial cohesion, while water content mainly affects the internal friction angle. (2) The softening model based on the classic rock damage model can better simulate the stress–strain relationship of the silt–steel interface under high normal stress and low water content. In contrast, the hardening model based on the classic hyperbola model can better simulate the stress–strain relationship under low normal stress and high water content. The calculated results of the softening/hardening model agree with the experimental results, and the model has 7 parameters. (3) The developed FRIC subroutine can effectively simulate the nonlinear mechanical behavior of the interface between silt and steel. The research results provide a reference for exploring the stability analysis of offshore structures considering interface weakening effects.

Stable oxic-anoxic transitional interface is beneficial to retard soil carbon loss in drained peatland - Liangfeng Liu; Jianqing Tian; Hongjun Wang; Dan Xue; Xinya Huang; Ning Wu; Meng Wang; Xingliang Xu; Changhui Peng; Yanfen Wang; Huai Chen (Soil Biology and Biochemistry, 2023)

Standard environmental evaluation framework reveals environmental benefits of green light optimized speed advisory: A case study on plug-in hybrid electric vehicles - Ning Wei; Zhenyu Jia; Xiaoyang Zhao; Lin Wu; Yanjie Zhang; Jianfei Peng; Ting Wang; Zhiwen Yang; Qijun Zhang; Hongjun Mao (Journal of Cleaner Production, 2023)

Deformation analysis of underwater shield tunnelling based on HSS model parameter obtained by the Bayesian approach - Yao Lu; Peng Yu; Yan Zhang; Jian Chen; Tao Liu; Han Wang; Hongjun Liu (Frontiers in Marine Science, 2023)
Deformation analysis and control of underwater large-diameter shield tunnels is a prerequisite for safe tunnel construction. Reasonable selection of constitutive model and its parameters is the key to accurately predicting the deformation induced by underwater shield tunnelling. In this paper, the finite element analysis of cavity expansion during the piezocone penetration test (CPTU) based on the hardening soil model with small strain stiffness (HSS) model was carried out, and the correlation model of the normalized cone tip resistance Q with the reference secant modulus E 50 ref and the effective internal friction angle φ ’ was established and verified using mini CPTU chamber test. Then, a Bayesian probability characterization approach for E 50 ref of silty clay based on CPTU was proposed. Furthermore, the deformation analysis of Jinan Yellow River tunnel crossing the south embankment was carried out to verify the reliability of the proposed approach. The good agreement between the field measurement and numerical simulation confirms that the parameters obtained by the Bayesian approach are reliable. Finally, a sensitivity analysis was performed to study the law of riverbed settlement induced by underwater large-diameter shield tunnelling. The results show that the increasing support pressure could effectively reduce the riverbed settlement, but there is an upper limit. The optimal support pressure of established model is between 0.45 MPa and 0.5 MPa. The uphill section causes greater riverbed settlement than the downhill section. Under the same condition, increasing buried depth and water level will lead to a more significant settlement.

Optical properties of vehicular brown carbon emissions: Road tunnel and chassis dynamometer tests - Chung Song Ho; Zongyan Lv; Jianfei Peng; Jinsheng Zhang; Tong-Hyok Choe; Qijun Zhang; Zhuofei Du; Hongjun Mao (Environmental Pollution, 2023)

Evaluating traffic emission control policies based on large-scale and real-time data: A case study in central China - Chao Zou; Lin Wu; Yanan Wang; Shida Sun; Ning Wei; Bin Sun; Jingwei Ni; Jing He; Qijun Zhang; Jianfei Peng; Hongjun Mao (Science of The Total Environment, 2023)

Comparison of CO2, NOx, and VOCs emissions between CNG and E10 fueled light-duty vehicles - Zongyan Lv; Lin Wu; Chao Ma; Luna Sun; Jianfei Peng; Lei Yang; Ning Wei; Qijun Zhang; Hongjun Mao (Science of The Total Environment, 2023)

A novel process for simultaneous biological nutrient removal and waste activated sludge reduction in one-stage system without aeration - Zhiwei Fan; Wei Zeng; Yuan Jia; Qingan Meng; Hongjun Liu; Hong Liu; Yongzhen Peng (Chemical Engineering Journal, 2023)

Experimental Investigation on the Cyclic Shear Mechanical Characteristics and Dynamic Response of a Steel–Silt Interface in the Yellow River Delta - Peng Yu; Jie Dong; Yong Guan; Qing Wang; Shixiang Jia; Meijun Xu; Hongjun Liu; Qi Yang (Journal of Marine Science and Engineering, 2023)
The shear behavior and dynamic response of a steel–silt interface are significant for the safety and stability of offshore structures in the Yellow River Delta. A series of steel–silt interface cyclic shear tests under constant normal load conditions (CNL) were carried out to explore the effects of normal stress, shear amplitude, roughness, and water content on the interface shear strength, shear stiffness, and damping ratio using a large interface shear apparatus. The preliminary results showed that the amplitude of normal stress and shear amplitude affected the interface’s shear strength, stiffness, and damping ratio in a dominant manner. The roughness and water content were also crucial factors impacting the rule of shear strength, shear stiffness, and damping ratio, changing with the number of cycles. Under various scenarios, the steel–silt interface weakened distinctively, and the energy dissipation tended to be asymptotic with the cyclic shear.

Tunnel measurements reveal significant reduction in traffic-related light-absorbing aerosol emissions in China - Chung Song Ho; Jianfei Peng; Zongyan Lv; Bin Sun; Lei Yang; Jinsheng Zhang; Jiliang Guo; Qijun Zhang; Zhuofei Du; Hongjun Mao (Science of The Total Environment, 2023)

Source apportionment of VOCs based on photochemical loss in summer at a suburban site in Beijing - Yajun Wu; Xiaolong Fan; Yan Liu; Jingqiao Zhang; Han Wang; Luna Sun; Tiange Fang; Hongjun Mao; Jun Hu; Lin Wu; Jianfei Peng; Shulan Wang (Atmospheric Environment, 2023)

Analysis of Cyclic Shear Stress–Displacement Mechanical Properties of Silt–Steel Interface in the Yellow River Delta - Peng Yu; Jie Dong; Haisong Liu; Rui Xu; Rujie Wang; Meijun Xu; Hongjun Liu (Journal of Marine Science and Engineering, 2022)
Pile foundations of offshore structures are often subjected to cyclic loads under storm loads, thus reducing their vertical bearing capacity. Therefore, studying the cyclic shear behavior of the soil–structure interface is important for maintaining the stability of offshore structures. A series of cyclic shear tests of the silt–steel interface were carried out using a large interface shear apparatus. The effects of various factors (i.e., normal stress, shear displacement amplitude, roughness, and water content) on the shear stress characteristics of the silt–steel interface were investigated. The stress–displacement model of the cyclic shear silt–steel interface was deduced. The results showed that the shear stress at the silt–steel interface was softened, and the type of bulk deformation was shear shrinkage under cyclic shear. With the increase in shear amplitude, the hysteresis curve gradually developed from “parallelogram” to “shuttle” and “hysteresis cake”. With the increase in normal stress and roughness and the decrease in water content, the interfacial shear strength, volume displacements growth rate, and growth rate increased. The stress–displacement mathematical model of the silt–steel interface based on the modified hyperbolic model was in good agreement with the test data.

Aberrant brain connectivity is associated with childhood maltreatment in individuals with major depressive disorder - Qianyi Luo; Juran Chen; Yuhong Li; Zhiyao Wu; Xinyi Lin; Jiazheng Yao; Huiwen Yu; Huawang Wu; Hongjun Peng (Brain Imaging and Behavior, 2022)

Scour Characteristics and Equilibrium Scour Depth Prediction around Umbrella Suction Anchor Foundation under Random Waves - Ruigeng Hu; Hongjun Liu; Hao Leng; Peng Yu; Xiuhai Wang (Journal of Marine Science and Engineering, 2021)
A series of numerical simulation were conducted to study the local scour around umbrella suction anchor foundation (USAF) under random waves. In this study, the validation was carried out firstly to verify the accuracy of the present model. Furthermore, the scour evolution and scour mechanism were analyzed respectively. In addition, two revised models were proposed to predict the equilibrium scour depth Seq around USAF. At last, a parametric study was carried out to study the effects of the Froude number Fr and Euler number Eu for the Seq. The results indicate that the present numerical model is accurate and reasonable for depicting the scour morphology under random waves. The revised Raaijmakers’s model shows good agreement with the simulating results of the present study when KCs,p

Effect of five modified mass selection cycles on combining ability in two Chinese maize populations - Hongjun Yong; Juan Tang; Xinzhe Zhao; Fengyi Zhang; Zhiyuan Yang; Yi Li; Mingshun Li; Degui Zhang; Zhuanfang Hao; Jianfeng Weng; Jienan Han; Bo Peng; et al. (Euphytica, 2020)

IVIG Delays Onset in a Mouse Model of Gerstmann-Sträussler-Scheinker Disease - Huiying Gu; Yvonne Kirchhein; Timothy Zhu; Gang Zhao; Hongjun Peng; Eileen Du; Junyi Liu; James A. Mastrianni; Martin R. Farlow; Richard Dodel; Yansheng Du (Molecular Neurobiology, 2019)

Control of NOx emissions by air staging in small- and medium-scale biomass pellet boilers - Yuening Li; Yingchao Lin; Jingbo Zhao; Boyang Liu; Ting Wang; Peng Wang; Hongjun Mao (Environmental Science and Pollution Research, 2019)

MCP1 triggers monocyte dysfunctions during abnormal osteogenic differentiation of mesenchymal stem cells in ankylosing spondylitis - Zhongyu Xie; Peng Wang; Jinteng Li; Yuxi Li; Shan Wang; Xiaohua Wu; Suhe Sun; Shuizhong Cen; Hongjun Su; Wen Deng; Zhenhua Liu; Yi Ouyang; et al. (Journal of Molecular Medicine, 2017)

Experimental evaluation of calcein and alizarin red S for immersion marking grass carp Ctenopharyngodon idellus - Hongjian Lü; Hongjun Chen; Mei Fu; Xiwen Peng; Dan Xi; Zhixin Zhang (Fisheries Science, 2015)

Biodegradation and Interaction of Quinoline and Glucose in Dual Substrates System - Peng Xu; Wencheng Ma; Hongjun Han; Baolin Hou; Shengyong Jia (Bulletin of Environmental Contamination and Toxicology, 2015)

Isolation of a Naphthalene-Degrading Strain from Activated Sludge and Bioaugmentation with it in a MBR Treating Coal Gasification Wastewater - Peng Xu; Wencheng Ma; Hongjun Han; Shengyong Jia; Baolin Hou (Bulletin of Environmental Contamination and Toxicology, 2015)

In vivo construction of tissue-engineered cartilage using adipose-derived stem cells and bioreactor technology - Hongjun Kang; Shibi Lu; Jiang Peng; Qiang Yang; Shuyun Liu; Li Zhang; Jingxiang Huang; Xiang Sui; Bin Zhao; Aiyuan Wang; Wenjing Xu; Quanyi Guo; et al. (Cell and Tissue Banking, 2015)

Grey matter volume abnormalities in patients with bipolar I depressive disorder and unipolar depressive disorder: a voxel-based morphometry study - Yi Cai; Jun Liu; Li Zhang; Mei Liao; Yan Zhang; Lifeng Wang; Hongjun Peng; Zhong He; Zexuan Li; Weihui Li; Shaojia Lu; Yuqiang Ding; et al. (Neuroscience Bulletin, 2015)

Association of Serum Bisphenol-A Concentration and Male Reproductive Function Among Exposed Workers - Wanli Zhuang; Kusheng Wu; Yukai Wang; Hongjun Zhu; Zanzhang Deng; Lin Peng; Guanghui Zhu (Archives of Environmental Contamination and Toxicology, 2015)

Factors affecting summer maize yield under climate change in Shandong Province in the Huanghuaihai Region of China - Guoqing Chen; Hongjun Liu; Jiwang Zhang; Peng Liu; Shuting Dong (International Journal of Biometeorology, 2012)

Reconstructions of annual summer precipitation and temperature in north-central China since 1470 AD based on drought/flood index and tree-ring records - Liang Yi; Hongjun Yu; Junyi Ge; Zhongping Lai; Xingyong Xu; Li Qin; Shuzhen Peng (Climatic Change, 2012)

The color reflectance of marine-terrigenous deposits in LZ908 borehole in south coastal plain of the Laizhou Bay - Na Zhao; Xingyong Xu; Hongjun Yu; Jing Yao; Qiao Su; Shuzhen Peng (Acta Oceanologica Sinica, 2011)